1993
DOI: 10.1016/0014-5793(93)80104-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and regulation of the angiotensin II type‐1 receptor (binding and mRNA) in human adrenal fasciculata‐reticularis cells

Abstract: The classical concept of human adrenal physiology indicates that only glomerulosa cells are the target of A-II. Herein, we demonstrated that cultured human adrenal fasciculata-reticularis cells were also responsive to this hormone. Indeed, these cells contained high affinity (Kd = 0.9-l. 1 nM) and low capacity (8,000-13,000 sites/cell) A-II receptors, and more than 95% of them were of the type-l. These AT1 receptors are functional since A-II was able to increase cortisol production after 48 h of treatment. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 28 publications
(7 reference statements)
1
17
0
Order By: Relevance
“…We also show that Ang II-induced aldosterone release could be totally blocked by losartan, indicating that Ang II is physiologically active in NCI-H295 cells by stimulation of an AT 1 receptor, as it has been previously demonstrated in this cell line and in human and rat adrenocortical cells. 9,26,27 The expression of AT 1 receptors and not AT 2 receptors could be confirmed by binding studies.…”
Section: Discussionmentioning
confidence: 71%
“…We also show that Ang II-induced aldosterone release could be totally blocked by losartan, indicating that Ang II is physiologically active in NCI-H295 cells by stimulation of an AT 1 receptor, as it has been previously demonstrated in this cell line and in human and rat adrenocortical cells. 9,26,27 The expression of AT 1 receptors and not AT 2 receptors could be confirmed by binding studies.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, these cells contain AT 1 receptor subtype and express AT1 receptor mRNA, and both receptor number and mRNA are negatively regulated by A-Il ( 18). Further evidence indicating that HAC are a target for A-II was given by the fact that the hormone increases the ACTH receptor mRNA levels in a dose-dependent manner, and that these effects are mediated mainly via transcriptional mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Ang II stimulates glucocorticoid release by enhancing the CRH-mediated ACTH release (Gaillard et al 1981, 1985, Abou-Samra et al 1986, Schoenenberg et al 1987 or by stimulating adrenal glucocorticoid production (Naville et al 1993). We recently demonstrated that Ang II increased the corticosterone responsiveness to CRH, an effect that was associated with an upregulation of the AT 1A receptor (Müller et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Over the last few years, it has been established that angiotensin II (Ang II) AT receptors (AGTR as listed in the MGI Database) are present in the organs of the hypothalamopituitary-adrenal (HPA) axis (Burson et al 1994, Gasc et al 1994, Llorens-Cortes et al 1994, Jöhren et al 1995, Jöhren & Saavedra 1996, that they are regulated during stress (Castren & Saavedra 1988, Aguilera et al 1995, Leong et al 2002, and that Ang II influences HPA axis reactivity by enhancing the synthesis and secretion of CRH, ACTH, and glucocorticoids (Rivier & Vale 1983, Abou-Samra et al 1986, Schoenenberg et al 1987, Sumitomo et al 1991, Naville et al 1993, Jezova et al 1998. This crosstalk between the renin-angiotensinaldosterone system (RAAS) and the HPA axis is functionally relevant for hypertension.…”
Section: Introductionmentioning
confidence: 99%